Mycotic aneurysm and it’s not so silent presentation – A case report - Shahanas, P; Sarada, Pooja Prathapan; Ganesh, K M; Chandan, Garud Suresh; Vijayan, Padmakumar Arayamparambil (Indian Journal of Case Reports, 2026)
We report a rare case of mycotic aneurysm of the aortic arch caused by Salmonella typhi, initially manifesting as hoarseness of voice secondary to left recurrent laryngeal nerve compression. A 58-year-old diabetic and hypertensive male presented with intermittent fever, initially managed as a urinary tract infection with diabetic ketoacidosis. Progressive symptoms led to the diagnosis of a saccular mycotic aneurysm of the aortic arch with purulent pericardial effusion and bilateral pleural effusions. Serology confirmed typhoid etiology. The patient was stabilized on antibiotics and referred for thoracic endovascular aortic repair. This case highlights the importance of considering vascular pathology in patients with unexplained vocal cord palsy and systemic infection, and underscores the need for early recognition and multidisciplinary management.